(untitled) (Eurasian Scientific Herald, 2022)
The article is devoted to the interdisciplinary study of modern problems of artistic creativity. Philosophical levels and aspects of the creative process are considered: cognitive, personal-motivational, cultural, and spiritual-systemic. It is also researched that artistic creativity by its nature is a reflexive process and is a phenomenon of spiritual culture. It is analyzed that high works of art are the result of conscious perception by the creator and a corresponding rise in emotions to the level of spiritual experience